PENGARUH SUBSTITUSI TEPUNG KEDELAI, TEPUNG BEKATUL DAN TEPUNG RUMPUT LAUT (Gracilaria sp) TERHADAP DAYA TERIMA, ZAT BESI DAN VITAMIN B12 BROWNIES[Effect of Soybean, Rice Bran, and Seaweed Flour (Gracilaria sp) Substitution on The Acceptibility, Iron and Vitamin B12 of Brownies] - Rahmasuci Fibriafi; Rita Ismawati (Media Gizi Indonesia, 2018)
Soybean, rice bran and seaweed flour (Gracilaria sp) are food sources of iron and vitamin B12 so it is potential to be used as an ingredient for alfernative snack for childbearing age women with ovo vegetarian diet. This research intended to analyze effect of soybean, rice bran and seaweed flour (Gracliaria sp) substitution on the acceptability, iron and vitamin B12 content. This research was true experimental research with completely randomized design. There are 4 formulas with six times replications. Analysis of accessibility different used was friedman. Friedman Test and Wilcoxon Ranks Test. The untrained panelists were 25 childberaing age women with ovo vegetarian diet. The difference test showed that there were no difference in colour, aroma and texture. There was a difference (p<0,05) on flavour characteristic and  Wilcoxon Ranks Test showed that there was a difference (p<0,05) between control formula and substitution formula. Based on the result of acceptability, brownies substitution formula with the best score was F3 formula (flour 37.5 g, soybean flour 22.5 g, rice bran 75 g, and seaweed flour (Gracilaria sp) 15 g). The iron and vitamin B12 content of  F3 formula were 3.6 mg and 0.2 μg respectively on 100 gram formula and fulfill 10-15% of childbearing age women’s requirement. Finally, the best formula which obtained from its acceptability, iron and vitamin B12 content was F3 formula, so it could be an alternative snack for childbearing age women with ovo vegetarian diet.